ANALISIS BEBAN KERJA TERHADAP KEBUTUHAN PEGAWAI ADMINISTRASI DALAM MENJAMIN OPTIMALISASI OPERASIONAL AKADEMIK - Yusuf, Yusuf; Anfas, Anfas (Jurnal MS, 2016)
The number of employees needs to be based on the workload of administrative staff UPBJJ-UTÂ Ternate. To calculate the activity time employees who used to work and time are not, researchers usingÂ work sampling table. Methods of calculating labor requirements are based on the calculation of theÂ workload with the approach per duties of office according MenPAN No. KEP/75/M.PAN/7/2004 onÂ Guidelines for Employee Needs Calculation based Workload in the framework of preparation of formation of civil servants. Samples were UPBJJ-UT Ternate employee status with the principalÂ administrative officer jobs based Target Achievement Quality Employees (CSKP). Calculation and dataÂ processing using Microsoft Excel. The study concluded that there is a significant result in the use ofÂ working time and to have the results of the number of employees needed for the actual number of employees, it is known that there are 7 functions of employees, unit administrative KTU has an excess number of employees as much as 1 employee and BPP has a shortage of employees as many as 1Â employee. For registration and testing PDA unit has a shortage of the number of employees as much as 1 employee. Â